Four key operations of communication and exchange in "mutual learning of civilizations"——On reducing and eliminating "cultural discounts" from the perspective of communication studies - Guoming, Yu; Mingjie, Wang; Zhuofan, Yang (International communication of Chinese culture, 2025)
The phenomenon of cultural discounts is ubiquitous. The so-called cultural discount is content of value deprivation in the decoding process. The discount phenomenon of information expression in the communication process involves four basic aspects: encoding deprivation during text compilation, transmission loss during channel communication, and cognitive loss and "cognition-processing" loss during user selection and user decryption. This paper discusses the four key communication points of cross-cultural communication in "Mutual Learning of Civilizations" from the perspective of communication studies, as well as the mechanism and operation logic of how to reduce and eliminate "cultural discounts".